Norman Mailer a double life - Lennon, Michael (New York Simon & Schuster, 2013)
The ?glorious?sweeping, full-scale biography? of Norman Mailer, the famous novelist, journalist, and public figure: ?There?s not a paragraph in this enormous book that doesn?t contain a nugget of something you?wish you had known? (The New York Times).
Includes bibliographical references (pages 907-914) and index.
Keywords: Mailer, Norman